2023
DOI: 10.12659/msm.940573
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking Endocrown Restoration Expertise Among Dentists: Insights from a Multi-Center Cross-Sectional Study

Mohammed M. Al Moaleem,
Nasser M. Al Ahmari,
Saeed M. Alqahtani
et al.

Abstract: Background This study, employing an online questionnaire, aimed to assess and contrast the awareness, knowledge, and perceptions of dentists in Saudi Arabia (SA) regarding endocrowns (EC) as post-endodontic restorations with those of dentists educated in various other countries. Material/Methods We conducted a cross-sectional survey among dental interns and practicing dentists in government facilities, private dental centers, and dental colleges in SA, including partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…The findings of the current survey revealed that the primary means of acquiring information on endocrown was through college, which contradicts the findings of Al Moaleem et al [21]. Their study reported that 45.97% of participants indicated that they obtained information about endocrown from friends, while only 25.04% leaned on college as a source of information.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of the current survey revealed that the primary means of acquiring information on endocrown was through college, which contradicts the findings of Al Moaleem et al [21]. Their study reported that 45.97% of participants indicated that they obtained information about endocrown from friends, while only 25.04% leaned on college as a source of information.…”
Section: Discussioncontrasting
confidence: 99%
“…This study is also consistent with the findings of Rasidi and Priscilla, who observed that 83.33% of the participants expressed that endocrown restorations are appropriate for molar teeth [23]. Moreover, Al Moaleem et al revealed that 61.23% of the participants expressed that endocrown restorations are appropriate for molar teeth [21]. According to a study conducted by Deepak and Nivedhitha, a majority of the participants, specifically 52.1%, expressed the belief that endocrown restorations are suitable for molar teeth [24].…”
Section: Discussionsupporting
confidence: 90%
“…This CAD/CAM material shows color stability for such patients, 27 , 28 and it is the most preferred material used by general practitioners in SA. 29 …”
Section: Discussionmentioning
confidence: 99%
“…More recently, the use of CAD/CAM for fabrication of prostheses has gained popularity [ 5 ]. Such prostheses are associated with good adaptation to biological tissues, excellent color stability, and superior physical and chemical endurance [ 6 , 7 ]. CAD/CAM-based zirconia crowns gained preference due to their strong resistance to occlusal forces and wear resemblance similar to natural teeth [ 8 ].…”
Section: Introductionmentioning
confidence: 99%